Exudative retinal detachment and macular hole as a rare sequelae of central vein occlusion - Rathna R,; Mushawiahti M.,; Mae-Lynn Catherine Bastion,; Masdar A,; Ropilah AR, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Central retinal vein occlusion (CRVO) is uncommon among young patients. Among the young adults, CRVO tends to be more benign with good visual prognosis. Macular oedema secondary to retinal vein occlusion is a relatively common complication that is currently being treated with intravitreal anti vascular endothelial growth factor with good outcomes. Other complications include lamellar hole,vitreous hemorrhage and neovascular glaucoma. We report a case of central retinal vein occlusion in a young female who presented to us with the complaint of blurring of vision in the left eye for four months. Fundus examination showed hyperemic optic disc, dilated tortuous vein, extensive retinal hemorrhages with macular oedema and an inferior shallow exudative retinal detachment. One month later, intravitreal ranibizumab injection for her macular oedema, a full thickness macular hole developed with reduction of macular oedema. Four months later, the hole spontaneously closed but her macular oedema persisted. The possibility of rare complications like exudative retinal detachment and full thickness macular hole must be kept in mind to ensure early detection and effective management is provided to preserve vision.